2021
DOI: 10.3390/genes12040526
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Subtype Recognition Based on Laplacian Rank Constrained Multiview Clustering

Abstract: Integrating multigenomic data to recognize cancer subtype is an important task in bioinformatics. In recent years, some multiview clustering algorithms have been proposed and applied to identify cancer subtype. However, these clustering algorithms ignore that each data contributes differently to the clustering results during the fusion process, and they require additional clustering steps to generate the final labels. In this paper, a new one-step method for cancer subtype recognition based on graph learning f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…MCCA is used as dimension reduction algorithms. We used the P values based on Cox log-rank model [43] to measure differential survival between the obtained subtype. With the decrease of P value, the subtype's survival rate is more significant, the clustering effect is more obvious.…”
Section: Comparison Algorithms and Evaluation Metricsmentioning
confidence: 99%
“…MCCA is used as dimension reduction algorithms. We used the P values based on Cox log-rank model [43] to measure differential survival between the obtained subtype. With the decrease of P value, the subtype's survival rate is more significant, the clustering effect is more obvious.…”
Section: Comparison Algorithms and Evaluation Metricsmentioning
confidence: 99%
“…This problem can be solved by using spectral clustering (Ng et al, 2001). Spectral clustering is a classical data clustering method and widely used in multiview clustering algorithms (Nie et al, 2016;Kang et al, 2020;Feng et al, 2021;Ge et al, 2021) the effectiveness of MRF-MSC, cancer subtypes prediction experiments were carried out on TCGA data sets. The results showed that MRF-MSC was able to obtain more significant clinical differences in cancer typing.…”
Section: Introductionmentioning
confidence: 99%